Ebola virus disease 2013-2014 outbreak in West Africa: An analysis of the epidemic spread and response - Cenciarelli, O; MALIZIA, ANDREA; Carestia, M; D'Amico, F; Sassolini, A; Giovanni, D; Rea, DA; Gabbarini, V; Tamburrini, VA; PALOMBI, LEONARDO; BELLECCI, CARLO; GAUDIO, PASQUALINO (International Journal of Microbiology, 2015)
TheEbola virus epidemic burst inWestAfrica in late 2013, started inGuinea, reached in a fewmonths an alarming diffusion, actually involving several countries (Liberia, Sierra Leone, Nigeria, Senegal, andMali). Guinea and Liberia, the first nations affected by the outbreak, have put in place measures to contain the spread, supported by international organizations; then they were followed by the other nations affected. In the present EVD outbreak, the geographical spread of the virus has followed a new route: the achievement of large urban areas at an early stage of the epidemic has led to an unprecedented diffusion, featuring the largest outbreak of EVD of all time.This has caused significant concerns all over the world: the potential reaching of far countries from endemic areas, mainly through fast transports, induced several countries to issue information documents and health supervision for individuals going to or coming fromthe areas at risk. In this paper the geographical spread of the epidemic was analyzed, assessing the sequential appearance of cases by geographic area, considering the increase in cases andmortality according to affected nations. The measures implemented by each government and international organizations to contain the outbreak, and their effectiveness, were also evaluated.